Definition of nasal provocation test and nasal allergen challenge, classification - Samoliński, Bolesław; Krzych-Fałta, Edyta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
The nasal provocation test can be defined as a method for restoring the response of the upper airway to natural exposure to allergens or irritants and for research on pathophysiology of the upper airway by testing potential biochemical mediators. A specific nasal provocation test (commonly known as nasal challenge with allergen) is used to examine the reaction of the immune system to an antigenic substance known as an allergen. It restores the response of the upper airway to natural exposure to allergens. The positive result of a specific nasal challenge test can be either IgE-dependent or cellular (eosinophilic). A non-specific nasal provocation test involves the application of substances or agents affecting the patient’s nasal epithelium without engaging the patient’s immune system. The test normally acts as a mediator, leading to a response of the sympathetic system, the parasympathetic system, the sensory system and receptors present in the nasal epithelium, e.g. histamine, leukotriene, prostaglandin and other receptors.